'Too Much, too Indigestible, too Fast'? The Decades of Struggle for Abortion Law Reform in Northern Ireland. Issue 4 (23rd April 2020) - Sheldon, Sally; O'Neill, Jane; Parker, Clare; Davis, Gayle
Abstract: In July 2019, the UK Parliament voted by an overwhelming majority for fundamental reform of Northern Ireland's archaic abortion laws. Regulations implementing the reform came into effect on 25 March 2020. Drawing on extensive archival resources and a small number of interviews, we locate this extraordinary political moment in a broader historical context. We explore the factors that blocked the possibility of reform in either Westminster or Stormont for over five decades and consider what it was that had changed in 2019 to render it possible. While the measure passed in Westminster represents a radical rupture with the past, we suggest that it was anything other than sudden, rather representing the culmination of decades of sustained campaigning. We conclude by briefly discussing what this change is likely to mean for the future.